Alcoholic fermentation of high‐gravity corn mashes with the addition of supportive enzymes. Issue 12 (17th April 2013) - Sapińska, Ewelina; Balcerek, Maria; Pielech‐Przybylska, Katarzyna
Abstract: Background: The main problem encountered during processing of cereals in distilleries, in particular by pressureless methods, is the relatively high viscosity of mashes that in turn retards their fermentation. It is caused by the extraction (along with starch) of pentosans, ß‐glucans, cellulose and hemicelluloses from cereal grains . Results: Experiments carried out within this work centered on the determination of the effect of treatment of corn mashes with xylanase, pullulanase, cellulase enzyme complex and cellobiase on chemical composition, viscosity of these mashes and yield of fermentation. The treatment with xylanase caused the greatest decrease in viscosity of the corn mash, by c . 41% in relation to the reference mash (9.08 ± 0.45 mPa s). In the mash digested with pullulanase the ethanol yield was increased from 70.85 ± 0.71% (reference mash) to 76.09 ± 0.76% of theoretical. The most beneficial impact on the synthesis of ethanol was afforded by the treatment of mashes with cellulase enzyme complex preparation. The yield of ethanol reached 79.59 ± 0.8% of theoretical productivity and the intake of sugars was 92.85 ± 0.93% . Conclusion: Under the optimal conditions found in these experiments, i.e. in corn mash supported with cellulase enzyme complex (CeluStar XL preparation) 61.69 ± 0.62 L of absolute ethanol could be obtained from 100 kg of starch. © 2013 Society of Chemical Industry